Attractiveness in African American and Caucasian Women: Is Beauty in the Eyes of the Observer? - Davis, Dawnavan S. (2009)
Traditional body image studies have been constrained by focusing on body thinness as the sole component of attractiveness. Evidence suggests that African American women may hold a multifactorial view of attractiveness that extends beyond size to include factors such as dress attire and race. The current study employed a culturally sensitive silhouette Model Rating Task (MRT) to examine the effects of attire, body size, and race on attractiveness. Unexpectedly, minimal differences on attractiveness ratings emerged by attire, body size, or model race between African American and Caucasian women. Overall, participants preferred the dressed, underweight, and African American models. Factors such as exposure to diverse groups and changes in African American culture may explain the present findings. Future studies to delineate the components of attractiveness for African American and Caucasian women using the MRT are needed to broaden our understanding and conceptualization of attractiveness across racial groups.